The American Colonial State in the Philippines : Global Perspectives - Foster, Anne L., 1965-; Go, Julian, 1970- (Book collections on Project MUSE., 2003)
Interdisciplinary collection placing the U.S. imperial project in the Philippines within a global, comparative framework.